Why art? The role of arts in arts and health - Vickhoff, Björn (Frontiers in Psychology, 2023)
“What is the evidence on the role of the arts in improving health and well-being?” This is the title of a World Health Organization report covering 3000 studies in the field of Arts and Health. The authors conclude that the arts do indeed have a robust impact on mental and physical health. Yet, the question of the role of the arts remains unanswered. What is and what is not an art effect? A theory is needed to define art, to validate research, to design experiments and to develop therapeutic techniques. There are many theoretical approaches in this interdisciplinary field, but so far no overarching theory concerning the role of the arts. Recently, embodied cognition has inspired articles on the perception of art. Although this approach is relevant to psychosomatic medicine, it has not yet received attention in the field of Arts and Health. This article presents a conceptual framework of art. It is based on embodied theory applied to aesthetic contextualism, leading to an understanding of art in terms of empathy. Key words: Aesthetic empathy, Arts and Health, aesthetic contextualism, enactment, embodied aesthetics, imagination, reuse, extended mind